The duality of the ego and the other in the poetry of Fahd Al-Askar (Damascus University Journal of arts and humanities sciences, 2023)
This study aimed to trace the duality of the ego and the other in the literature of the contemporary Kuwaiti poet Fahd Saleh Al-Askar, and used the inductive and analytical method. and how the poet documented these transformations in his poetry.Fahd Al-Askar was open-minded, free from the constraints of society. Rather, he rejected many of his habits and behaviors, and this tendency to liberation and challenge made him confront a group of society that adheres to inherited traditions and sanctifies them and sees deviation from them as immorality, which made the dispute turn into a great conflict and hostility between the two parties. Each of them is a stranger, hated and unacceptable, and a threat to his existence and himself. The importance of Fahd Al-Askari’s poetic experience lies in being evidence of the diversity of intellectual life in Kuwait at that period, and an example of what a poet looking forward to a better reality can be, a reality that does not call to deny the different other or try to abolish it, but rather recognize andrespect it.
Keywords: Ego; Other; Kuwaiti POETRY; AL ASKAR